Role of handgrip strength in predicting the quality of life in older adults: A cross-sectional study - Masoumeh Eskandarzadeh; Roya Mansour-Ghanaei; Parand Pourghane; Bahare Gholami Chaboki (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Quality of life (QOL) is a vital component in assessing the standard of living for seniors. Hand grip strength (HGS) is a widely used measure to diagnose muscle strength decline that often occurs due to age-related loss of skeletal muscle mass and function. This study focuses on the HGS in predicting the QOL of older adults who are referred to retirement centers in Guilan Province. MATERIALS AND METHODS: In 2021, a cross-sectional analytical study was conducted among 115 older adults who were residing in retirement centers located in Guilan Province, Northern Iran. The participants were selected using a two-stage sampling method, where three retirement centers were randomly chosen followed by convenience sampling from each center. The selected retirement centers were situated in Langrod, Sowme'eh Sara, and Rasht cities in the east, west, and center of the province, respectively. The data were collected through a demographic information questionnaire, QOL scale (CASP-19), and HGS measurement using a dynamometer. RESULTS: Of the participants, 57.4% were male, 51.3% had middle income, and 96.5% were categorized as young elderly. The mean overall QOL score was found to be 37.026 ± 6.123, while the mean HGS level was 31.74 ± 7.45 and 18.48 ± 5.13 among males and females, respectively. There was a significant association between the level of education and QOL (P = 0.002). Moreover, there was a positive and significant correlation between HGS and QOL (r = 0.54, P = 0.001). The results of the multiple linear regression identified HGS as a predictor of QOL (Adj R2 = 0.44, βHGS = 0.79). CONCLUSION: Given that HGS has been identified as a predictor of QOL in older adults, improving this factor through exercise can lead to enhancement in their QOL. Therefore, regular sports exercises can be recommended as a means of improving HGS and subsequently enhancing the QOL of older adults.